2016
DOI: 10.1038/hr.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

Circadian blood pressure changes and cardiovascular risk in elderly-treated hypertensive patients

Abstract: The independent prognostic significance of circadian blood pressure (BP) changes is unclear. We investigated the association between circadian BP changes and cardiovascular risk among elderly-treated hypertensive patients. The occurrence of a composite end point (that is, stroke, coronary events, heart failure and peripheral revascularization) was evaluated among 1191 elderly-treated hypertensive patients (age range 60-90 years). According to the nighttime change and the morning surge (MS) of systolic BP, subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 58 publications
0
35
1
3
Order By: Relevance
“…The reduction in nocturnal BP seen in this study is consistent with the suggestion that changes in BP during treatment with an SGLT2 inhibitor restore disrupted circadian BP rhythms, shifting patients with hypertension and diabetes from a nondipper to a dipper pattern. 30,31 Given the association between disrupted circadian BP patterns and cardiovascular events, [32][33][34][35] this is one plausible mechanism for the beneficial effects of SGLT2 inhibitor treatment on cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in nocturnal BP seen in this study is consistent with the suggestion that changes in BP during treatment with an SGLT2 inhibitor restore disrupted circadian BP rhythms, shifting patients with hypertension and diabetes from a nondipper to a dipper pattern. 30,31 Given the association between disrupted circadian BP patterns and cardiovascular events, [32][33][34][35] this is one plausible mechanism for the beneficial effects of SGLT2 inhibitor treatment on cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…People with extreme dipping also had a higher probability of developing a morning surge phenomenon (an excessive increase in blood pressure in the early hours of the morning). Since morning surge is associated with an increased risk of developing stroke and other cardiovascular diseases [51,52], it would be interesting to explore more psychological risk factors associated with this pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In hypertensive patients, as well as in general populations, some studies observed a negative prognostic impact of MS, whereas others did not. These discrepancies may be related to the characteristics of the studied population, that is, normotensive or hypertensive, young or old, untreated or treated, and to ethnic differences, methodological issues, and the confounding relationship of MS with other features of 24‐hour BP profile, such as nighttime BP pattern …”
Section: Introductionmentioning
confidence: 99%
“…Some investigators assessed the association between MS of BP and future cardiovascular events, both in hypertensive patients and in general populations . The available evidence, however, is not homogeneous .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation